Purpose statements in experimental doctoral dissertations submitted to US universities: An inquiry into doctoral students' communicative resources in language education - Lim, J.M.H.; Loi, C.K.; Hashim, A.; Liu, M.S.M. (2015)
While it is widely known that purpose statements are generally incorporated in dissertations and academic journal papers, graduate student writers often encounter difficulties in the writing of such crucial statements. This paper looks into the extent to which doctoral candidates use inter-move shifts to strategically arrive at their purpose statements, and how they employ communicative resources to construct such pivotal statements that drive their entire studies. Based on an analytical framework developed by Swales (1990; 2004) and relevant qualitative data provided by specialist informants, we have analysed a corpus of experimental doctoral dissertations submitted to 32 American universities within a period of 10 years in order to ascertain (i) the degree to which research purpose is presented in dissertation introductions, (ii) how preceding rhetorical segments are strategically connected with purpose statements, and (iii) the ways in which prominent lexico-grammatical structures are used to attain strategic communicative functions. The findings of this study have illustrated how instructors in English for Academic Purposes (EAP) can possibly prepare relevant teaching materials aimed at guiding learners to present the foundational segments that determine the overall direction of their studies. (C) 2015 Elsevier Ltd. All rights reserved.